Diet Diversity to Assess Diet Quality of Pre-Conception Women in Bekasi, West Java - Arindah Nur Sartika; Tri Marta Fadhilah (Ikatan Sarjana Gizi Indonesia (ISAGI), 2021)
Pre-conception women have important role to determine children nutritional status. Children with good nutritional status are born from mothers who have good diet. Diversified diet also can prevent woman to suffer from chronic energy malnutrition and anemia during pregnancy. This study aims to assess diet quality of pre-conception women in Kota Bekasi, West Java. The study conducted as observational study design, specifically using cross sectional approach. About 105 “bride to be” from 8 Religious Affairs Office in Kota Bekasi, West Java, Indonesia was joined the study. Respondents were interviewed with structured questionnaire consist of social economic characteristics and dietary intake. Dietary assessment was done using 24-h food recall to fill Minimum Dietary Diversity for Women of reproductive Age (MDD-W) questionnaire. The result showed out of 10 food groups, median consumption of food groups consumed by respondents was 4 food groups, also as the highest proportion of total food group (36.19%), followed by 5 food groups (25.71%), and 3 food groups (21.90%). Maximum score of dietary diversity is 8 (0.95%), and minimun score is 2 (3.81%). Meanwhile, most consumed food group was staple foods (99.05%). Nuts and seeds were the least proportion of food group (3.81%) consumed by respondents. There was around one-third (38.10%) of the respondents consumed total food group below recommended score (<5). Diet diversity of pre-conception women should be improved. To prevent from malnutrition, pre-conception women are suggested to vary their diet. Nutrition education during premarital class/ consultation is recommended.